Business growth mentorship for female-owned enterprises in South Africa - Karabo Lekoloane; Anastacia Mamabolo; Gloria Mbokota (South African Journal of Business Management, 2025)
Purpose: This study examines the role of mentorship offered to female entrepreneurs during the growth phase of their businesses. Applying social cognitive theory (SCT), we examine the personal, behavioural and environmental factors that contribute to learning outcomes as a result of a mentoring relationship.